2013
DOI: 10.1186/1751-0147-55-31
|View full text |Cite
|
Sign up to set email alerts
|

Acute non-ambulatory tetraparesis with absence of the dens in two large breed dogs: case reports with a radiographic study of relatives

Abstract: BackgroundNon-ambulatory tetraparesis with an absence of the dens of C2 (axis) has not previously been reported in large breed dogs. An absence or hypoplasia of the dens has been reported in both small, medium and large breed dogs, but not in closely related animals.MethodsTwo young large-breed dogs (a German shepherd and a Standard poodle) both with an acute onset of non-ambulatory tetraparesis were subjected to physical, neurological and radiographic examinations. Both dogs were euthanased and submitted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…AAI has been reported not only in small-sized dogs, but also in large-sized dogs and cats [12, 27, 32, 35]. AAI occurs, because of congenital dysplasia of the atlantoaxial joint (AAJ), including odontoid hypoplasia, non-fusion, incomplete ossification and malformation, as well as acquired trauma-related instability, subluxation or dislocation (fracture or ligament rupture) [6, 16].…”
mentioning
confidence: 99%
“…AAI has been reported not only in small-sized dogs, but also in large-sized dogs and cats [12, 27, 32, 35]. AAI occurs, because of congenital dysplasia of the atlantoaxial joint (AAJ), including odontoid hypoplasia, non-fusion, incomplete ossification and malformation, as well as acquired trauma-related instability, subluxation or dislocation (fracture or ligament rupture) [6, 16].…”
mentioning
confidence: 99%
“…Complete absence or hypoplasia of the dens is a predisposing congenital anomaly in toy breed dogs and has been recently reported in a family of Standard Poodles (12).…”
Section: Discussionmentioning
confidence: 98%
“…According to these issues, it is suggested that absence of dens allows dorsal angulation of axis by lose their functional ability of alar ligaments. In fact, some AAS patients with dorsal subluxation of C2 with deficit of the dens have been reported (Patton et al, 2010;Stigen et al, 2013). Therefore, the patient who has AAS with absence of dens shows higher opportunity to dorsal subluxation of C2 than normal AAS patients.…”
Section: Introductionmentioning
confidence: 93%